HUBUNGAN DUKUNGAN SOSIAL SUAMI TERHADAP KESUKSESAN KARIR SUBJEKTIF PADA WANITA KARIR - Yudanta Putri, Fara; Malahati , Fildzah (Jurnal Psimawa : Diskursus Ilmu Psikologi dan Pendidikan, 2025)
Subjective career success is an individual's assessment of the achievement of career goals and the individual's sense of satisfaction in the career they have chosen. One factor that can support an individual in achieving this success is the husband's social support. This study aims to determine the relationship between husband's social support and subjective career success in career women. This study used a quantitative approach with a survey method and obtained data from 96 respondents obtained through questionnaires. This study used the Spearman Rho correlation test. The results of this study indicate that husband's social support has a 61.9% influence on subjective career success in career women, which can be interpreted as meaning that the higher the husband's social support, the higher the subjective career success of career women.